A suggestion for simplifying the theory of asset prices - Riccardo Cesari; Carlo D'Adda (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2005)
Using an ordinal approach to utility, in the spirit of Hicks (1962, 1967a), it is possible to greatly simplify the theory of asset prices. The basic assumption is to summarize any probability distribution into its moments so that preferences over distributions can be mapped into preferences over vectors of moments. This implies that assets, like Lancaster's (1966) consumption goods, are bundles of characteristics and can be directly priced, at the margin, in terms of the market portfolio. Expected utility is not required and both St.Petersburg and Allais paradoxes may be easily solved.
Keywords: 330; CAPM; Nutzenfunktion